Mapping the uneven temporal changes in ordinary and extraordinary rainfall extremes in Italy - Paola Mazzoglio; Alberto Viglione; Daniele Ganora; Pierluigi Claps (Journal of Hydrology: Regional Studies)
Study region: Italy Study focus: The impact of climate change on the hydrological cycle is a debated topic, especially in complex areas such as the Mediterranean. Among all the European countries, Italy represents a challenging study area due to its complex topography, variable climate conditions, and the presence of fragmented datasets produced by different regional services. In this work, time series of sub-daily annual maximum rainfall depths coming from the ''Improved Italian – Rainfall Extreme Dataset'' are used to shed light on the possible presence of trends in rainfall extremes and their magnitude. Two different approaches are used: an at-site application of the Mann-Kendall test, combined with the computation of the Sen’s slope estimator, and a distributed application of quantile regressions, which allows to cover the entire period of the analysis and to investigate the rate of change in the largest extremes. New hydrological insights for the region: The median values of short-duration annual maxima show an increase all over the country, especially when considering 1 h extremes. Negative trends emerge in some areas when moving to longer durations (24 h). The quantile regressions show that higher quantiles (0.95–0.99 exceedance probability) are characterized by larger variations with respect to lower quantiles (i.e., the median). The non-uniformity of the observation records, finally, demonstrates the need for caution in deriving ultimate conclusions in emerging trends all over the country.